2016
DOI: 10.5194/se-7-141-2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vegetation restoration on the aggregate stability and distribution of aggregate-associated organic carbon in a typical karst gorge region

Abstract: Abstract. Land use changes have a major impact on soil structure and soil nutrients. The influences of vegetation restoration on aggregate stability and soil carbon storage have been studied extensively, but the distribution of aggregate-associated carbon is not yet understood. The objective of this work was to study the influences of vegetation restoration on aggregate stability and distribution of soil organic carbon (SOC) associated with water-stable aggregates (WSAs) in a karst gorge region. The experiment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…The loss of this fundamental organic material to soil structure causes lower stability in the aggregates (Tang et al, 2016), facilitating higher rates of erosion and contributing to the eutrophication of lakes and rivers by nutrient transportation, particularly of phosphorus and nitrogen (Kurz et al, 2005;Li et al, 2006). This correlation was also observed by Li et al (2006).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The loss of this fundamental organic material to soil structure causes lower stability in the aggregates (Tang et al, 2016), facilitating higher rates of erosion and contributing to the eutrophication of lakes and rivers by nutrient transportation, particularly of phosphorus and nitrogen (Kurz et al, 2005;Li et al, 2006). This correlation was also observed by Li et al (2006).…”
Section: Discussionsupporting
confidence: 58%
“…In line with these results, Trabaquini et al (2015) showed that land degradation in Brazilian savannah (Cerrado) has altered the soil's physical attributes, increasing runoff; bulk density and penetration resistance, whereas air permeability and porosity decreased. Tang et al (2016) observed that areas with larger aboveground biomass have higher aggregate stability which has correlation with erosion-related variables, especially soil erodibility (Stanchi et al, 2016). The observed reduction of ΔOC and increased land cover may be an indication of an increase in the carbon stock in H F , which improved soil's physical conditions such as aggregate stability, infiltration, porosity and water storage capacity (Stanchi et al, 2016;Costantini et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These results were consistent with that of the previous study (Zhang et al 2014). However, some studies showed that the highest SOC content was in clay-silt aggregate, and the lowest was in macro-aggregate (Gao et al 2013, Tang et al 2016.…”
Section: Effects Of N Addition On Soc Contentsupporting
confidence: 93%
“…A large number of studies found that GRSP and SOC were significantly correlated with MWD because both can bind soil particle for aggregate formation (Rillig 2004, Wright et al 2007, Baldock, Kay and Schnitzer 1987. However, recent studies found that GRSP and/or SOC may have no significant relationship with MWD (Wu et al 2013, Li et al 2005, Leelamanie and Mapa 2015) because aggregate stability was not only affected by GRSP and SOC contents but also by soil texture, human disturbance, and other factors (Wei et al 2011, Tang et al 2016. In our study, the contents of GRSP and SOC significantly changed, but MWD insignificantly changed with N addition levels which caused insignificant relationships among MWD, GRSP, and SOC.…”
Section: Relationships Among Grsp Soc and Aggregate Stabilitymentioning
confidence: 99%